2018
DOI: 10.1161/jaha.118.009974
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Oxygen Consumption and Efficiency in Patients With Cardiac Amyloidosis

Abstract: Background This study evaluated myocardial oxygen consumption (MVO 2 ) and myocardial external efficiency (MEE) in patients with cardiac amyloidosis (CA). Furthermore, we compared MEE and MVO 2 in subjects with light chain amyloidosis versus transthyretin (ATTR) amyloidosis. Methods and Results The study population comprised 40 subjects: 25 patients with confirmed CA and 15 control subjects. All subjects underwent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…This method has been used in patients with heart failure and prediction of response to cardiac resynchronization therapy, as well as in patients with confirmed or suspected coronary artery disease 6‐9 . Clemmensen et al 10 reported significant correlation between echocardiography‐derived myocardial work and myocardial external efficiency evaluated by positron emission tomography in patients with cardiac amyloidosis, which supports use of echocardiography in evaluation of myocardial work and confirms that cardiac catheterization is not the only adequate method for assessment of myocardial work.…”
Section: Introductionmentioning
confidence: 92%
“…This method has been used in patients with heart failure and prediction of response to cardiac resynchronization therapy, as well as in patients with confirmed or suspected coronary artery disease 6‐9 . Clemmensen et al 10 reported significant correlation between echocardiography‐derived myocardial work and myocardial external efficiency evaluated by positron emission tomography in patients with cardiac amyloidosis, which supports use of echocardiography in evaluation of myocardial work and confirms that cardiac catheterization is not the only adequate method for assessment of myocardial work.…”
Section: Introductionmentioning
confidence: 92%
“…309,330 Moreover, it has been reported that differences in strain values between LV apex and basal increased by using exercise stress echocardiography, and this difference in strain values was related to symptoms in patients with CA (e.g., NYHA class, metabolic equivalents at peak exercise, maximum V O2). 331 Apical sparing is observed both in patients with ATTR amyloidosis and in those with AL amyloidosis. However, the strain value at the LV apex in patients with ATTR amyloidosis has been shown to be lower than that in patients with AL amyloidosis.…”
Section: What Are Echocardiographic Findings To Recommend the Use Of Tafamidis?mentioning
confidence: 99%
“…The link between impaired exercise capacity and central hemodynamic alterations has been extensively studied in patients with CA ( 9 12 ). Typically, CA is predominantly considered a diastolic disease caused by increased myocardial stiffness and restrictive heart wall chamber behavior ( 9 ).…”
Section: Central Hemodynamic Adaptation To Exercise In Cardiac Amyloi...mentioning
confidence: 99%
“…Typically, CA is predominantly considered a diastolic disease caused by increased myocardial stiffness and restrictive heart wall chamber behavior ( 9 ). Recent studies have also underlined a profound lack of myocardial contractile reserve and coronary flow velocity reserve ( 10 12 ). A blunt increase in stroke volume during exercise has been attributed to this decreased contractile reserve, rather than changes in preload and afterload ( 10 ).…”
Section: Central Hemodynamic Adaptation To Exercise In Cardiac Amyloi...mentioning
confidence: 99%